Evolusi Hukum Waris dalam Perspektif Islam: Dari Masa Jahiliah Hingga Konsep Kewarisan Bilateral Hazairin - Dian Lestari (Yayasan Cendekia Gagayunan Indonesia, 2024)
The Qur'an provides clear guidance on the matter of inheritance, as set forth in the Surah An-Nisa. The transfer of property from the deceased to the living in Islamic inheritance law is comprised of three elements: the heir, the inheritance, and the heirs. The scope of this research concerns the problem of the management and settlement of an estate, including the continuation of the rights and obligations of the deceased to the heirs left behind. This research will examine the development of inheritance arrangements in Islamic law. It will also examine the determination of Qath'i Ta'abbudi Inheritance, restrictions on Wasiat in Islamic Inheritance Law, the concept of justice in Islamic Inheritance Law and the Bilateral Inheritance Model in the perspective of Islamic Inheritance Law. This approach employs the philosophical tenets of Islamic family law to address contemporary concerns such as gender equality and the adaptation of family law in Islamic inheritance in modern society. This approach aims to explore the topic by aligning the main perspectives of Islamic inheritance in philosophy with related literature that supports a more comprehensive analysis. Furthermore, it seeks to comprehend the rationale, moral, and divine purpose behind the family law rules set out in the sharia. The settlement of the estate determines who is the heir, who is entitled to a share of the inheritance, how much their respective shares are, and how the provisions of the division of the inheritance are determined.